Dialogic Education and Technology - Wegerif, Rupert (Springer, 2017)
Dialogic Education and Technology is about using new technology to draw people into the kind of dialogues which take them beyond themselves into learning, thinking and creativity. The program of research reported in this book reveals key characteristics of learning dialogues and demonstrates ways in which computers and networks can deepen, enrich and expand such dialogues. A dialogic perspective is developed drawing upon recent work in communications theory, psychology, computer science and philosophy. This perspective foregrounds the creative space opened up by authentic dialogues. Whereas studies of computer-supported collaborative learning have tended to see dialogue as a means to the end of knowledge construction the dialogic perspective taken by this book sees dialogue as an end in itself - in fact moving learners into the space of dialogue is described as the core aim of education. The central argument of the book is that there is a convergence between this dialogic perspective in education and the affordances of new information and communications technology. A genuinely dialogic perspective is relatively new to the field of educational technology and there is a considerable amount of interest in this topic amongst researchers who wish to see what extra insights, if any, a dialogical approach can offer them. "This is an exciting book that synthesizes, clarifies and extends mounting discussions of dialogical thinking related to computer-supported education [...]. It is not only a delightful personal statement, but provokes thought on central issues of CSCL and enters into challenging dialog with the relevant alternative approaches. As a result of reading this book, I am convinced that we urgently need to open new online spaces for people to understandingly interact with different perspectives and creatively generate new insight and respect for difference." -Gerry Stahl Executive Editor of the International Journal of Computer Supported Collaborative Learning